Practical guidelines for nursing and midwifery diabetes care – 2026. A position of the Polish Federation for Education in Diabetology - Szewczyk, Alicja; Tobiasz-Kałkun, Natasza; Stefanowicz-Bielska, Anna; Kobos, Ewa; Kapuściok , Justyna; Karczewska, Agnieszka; Mazuryk, Kamila; Hornik, Beata (Nursing in the 21st Century, 2025)
Aim. Presenting a set of procedures describing nursing interventions in diabetes care, including currently available scientific evidence and clinical experience of specialists involved in the care of diabetic patients.Material and methods. The study involved a literature review of selected areas of nursing practice in diabetes care. When compiling the material, the priority was to use data from: randomized controlled clinical trials and their meta-analyses, systematic reviews, observational studies and other studies with lower levels of evidence.Results. Based on an analysis of the collected material, 14 procedures and 4 guidelines have been developed, describing selected aspects of nursing interventions in diabetic patients. Each of the procedures details key recommendations on diabetes care, arranged in accordance of the significance ascribed to the scientific evidence analyzed.Conclusions. The 2026 PFED guidelines on nursing diabetes care are the effect of the evaluation of the previous versions and comprise an updated, considerably more extensive, comprehensive and evidence-based set of practices. The major asset of these guidelines is their interdisciplinarity, reflected in the fact that the final version of the publication was approved by consultants in nursing fields, a consultant in diabetology, and representatives of the medical community from the Polish Diabetes Society. The authors experience gained during work on international recommendations (New Insulin Delivery Recommendations) played an important role when formulating the present guidelines.